Carmustine Wafers Implantation in Patients With Newly Diagnosed High Grade Glioma: Is It Still an Option? - Ricciardi, Luca; Manini, Ivana; Cesselli, Daniela; Trungu, Sokol; Piazza, Amedeo; Mangraviti, Antonella; Miscusi, Massimo; Raco, Antonino; Ius, Tamara (Frontiers in Neurology, 2022)
Background The implantation protocol for Carmustine Wafers (CWs) in high grade glioma (HGG) was developed to offer a bridge between surgical resection and adjuvant treatments, such as radio- and chemotherapy. In the last years, however, a widespread use of CWs has been limited due to uncertainties regarding efficacy, in addition to increased risk of infection and elevated costs of treatment. Objective The aims of our study were to investigate the epidemiology of patients that underwent surgery for HGG with CW implantation, in addition to the assessment of related complications, long-term overall survival (OS), and associated prognostic factors. Methods Three different medical databases were screened for conducting a systematic review of the literature, according to the PRISMA statement guidelines, evaluating the role of BCNU wafer implantation in patients with newly diagnosed HGG. The search query was based on a combination of medical subject headings (MeSH): “high grade glioma” [MeSH] AND “Carmustine” [MeSH] and free text terms: “surgery” OR “BCNU wafer” OR “Gliadel” OR “systemic treatment options” OR “overall survival.” Results The analysis of the meta-data demonstrated that there was a significant advantage in using CWs in newly diagnosed GBM in terms of OS, and a very low heterogeneity among the included studies [mean difference 2.64 (95% CI 0.85, 4.44); p = 0.004; I2149 = 0%]. Conversely, no significant difference between the two treatment groups in terms of PFS wad detected (p = 0.55). The analysis of complications showed a relatively higher rate in Carmustine implanted patients, although this difference was not significant (p = 0.53). Conclusions This meta-analysis seems to suggest that CWs implantation plays a significant role in improving the OS, when used in patients with newly diagnosed HGG. To minimize the risk of side effects, however, a carful patient selection based mainly on patient age and tumor volume should be desirable.